Neuromuscular dysfunction with the experimental arm acting as its own reference following eccentric and isometric exercise - Philippou, A., Bogdanis, G.C., Maridaki, M. (Somatosensory and Motor Research, 2010)
Eccentric exercise has been extensively used as a model to study muscle damage-induced neuromuscular impairment, adopting mainly a bilateral matching task between the reference (unexercised) arm and the indicator (exercised) arm. However, little attention has been given to the muscle proprioceptive function when the exercised arm acts as its own reference. This study investigated muscle proprioception and motor control, with the arm acting both as reference and indicator, following eccentric exercise and compared them with those observed after isometric exercise. Fourteen young male volunteers were equally divided into two groups and performed an eccentric or isometric exercise protocol with the elbow flexors of the non-dominant arm on an isokinetic dynamometer. Both exercise protocols induced significant changes in indicators of muscle damage, that is, muscle soreness, range of motion and maximal isometric force post-exercise (p < 0.050.001), and neuromuscular function was similarly affected following both protocols. Perception of force was impaired over the 4-day post-exercise period (p < 0.001), with the applied force being systematically overestimated. Perception of joint position was significantly disturbed (i.e., target angle was underestimated) only at one elbow angle on day 4 post-exercise (p < 0.05). The misjudgements and disturbed motor output observed when the exercised arm acted as its own reference concur with the view that they could be a result of a mismatch between the central motor command and an impaired motor control after muscle damage. © 2010 Informa Healthcare Ltd.